2022
DOI: 10.1007/s00277-022-04906-8
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of probabilistic graphical models for early detection of SARS-CoV-2 reactive antibodies after SARS-CoV-2 vaccination in hematological patients

Abstract: Prior studies of antibody response after full SARS-CoV-2 vaccination in hematological patients have confirmed lower antibody levels compared to the general population. Serological response in hematological patients varies widely according to the disease type and its status, and the treatment given and its timing with respect to vaccination. Through probabilistic machine learning graphical models, we estimated the conditional probabilities of having detectable anti-SARS-CoV-2 antibodies at 3-6 weeks after SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Both conditions may facilitate the virus entry and in particular its spread. Although the use of anti-CD20 monoclonal antibodies has been consistently associated with a lower amount of SARS-CoV-2-R-A after vaccination [29][30][31][32], being treated with anti-CD20 monoclonal antibodies was not associated with an increased incidence of breakthrough infection in our study. It is likely that the number of events and in particular of patients who received anti-CD20 monoclonal antibodies within 6 months before starting vaccination (n = 97, 36%) was too low to observe significant differences.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Both conditions may facilitate the virus entry and in particular its spread. Although the use of anti-CD20 monoclonal antibodies has been consistently associated with a lower amount of SARS-CoV-2-R-A after vaccination [29][30][31][32], being treated with anti-CD20 monoclonal antibodies was not associated with an increased incidence of breakthrough infection in our study. It is likely that the number of events and in particular of patients who received anti-CD20 monoclonal antibodies within 6 months before starting vaccination (n = 97, 36%) was too low to observe significant differences.…”
Section: Discussioncontrasting
confidence: 68%
“…Several prior studies revealed that among HD patients, CLL patients are characterized by a severe cellular immune dysfunction which translates into a low humoral response rate [24,25] and a severe course of the disease [26,27], although a significant reduction in mortality has been observed in the Omicron era [28]. On the other hand, corticosteroid use has been associated with a lower probability of mounting an adequate humoral response [29]. Both conditions may facilitate the virus entry and in particular its spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prospective, observational, multicenter registry study was conducted by the Infectious Complications Subcommittee (GRUCINI) of the Spanish Hematopoietic Stem Cell Transplantation and Cell Therapy Group (GETH-TC). Characteristics of the registry have been published elsewhere in detail [ 4 , 12 ]. Briefly, the registry included consecutive hematological disorders (HD) patients who were vaccinated against SARS-CoV-2 between December 30, 2020 and June 30, 2021 in 21 participating Spanish centers.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative incidence of SARS-CoV-2 breakthrough infection at one year after full vaccination was 15.3% [95%, confidence interval (C.I. ), [12][13][14][15][16][17][18]. Cumulative incidence was similar among cell procedures: 21% (95%, C.I.…”
Section: Sars-cov-2-reactive Igg Antibody Kinetics Before Boostermentioning
confidence: 99%